Natural Course of Orbital Roof Fractures. Issue 4 (December 2014) - Stam, Liselotte H. M.; Wolvius, Eppo B.; Schubert, Warren; Koudstaal, Maarten J.
The natural course of several isolated and nonisolated orbital roof fractures is reported, by showing four cases in which a "wait and see" policy was followed. All four cases showed spontaneous repositioning and stabilizing of the fracture within less than a year. This might be explained by the equilibrium between the intraorbital and intracranial pressures.